2016
DOI: 10.18632/oncotarget.9878
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical effects of CRLX101, an investigational camptothecin-containing nanoparticle drug conjugate, on treating glioblastoma multiforme via apoptosis and antiangiogenesis

Abstract: Malignant gliomas are difficult to treat in clinical practice. This study was aimed to investigate the preclinical efficacy of CRLX101, an investigational nanoparticle-drug conjugate developed by conjugating camptothecin (CPT) with cyclodextrin-polyethylene glycol, against gliomas. CPT fluorescence was detected across tight-junction barriers and in mouse plasma and brain. Following CRLX101 treatment, CPT was distributed in the cytoplasm of human U87 MG glioma cells. U87 MG cell viability was decreased by CRLX1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 42 publications
1
54
0
Order By: Relevance
“…Human U‐87 MG and GBM8401 cells used in this study were provided by Professor Ruei‐Ming Chen, Taipei Medical University, Taiwan and Professor Jing‐Gung Chung, China Medical University, Taiwan, respectively. Cells were maintained in MEM medium or RPMI‐1640 medium with 10% FBS, 100 IU/mL penicillin, 100 mg/mL streptomycin and 1 mmol/L sodium pyruvate, and then incubated at 37°C in a humidified atmosphere of 5% CO 2 . Cells were grown to 70%‐80% confluence before drug treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Human U‐87 MG and GBM8401 cells used in this study were provided by Professor Ruei‐Ming Chen, Taipei Medical University, Taiwan and Professor Jing‐Gung Chung, China Medical University, Taiwan, respectively. Cells were maintained in MEM medium or RPMI‐1640 medium with 10% FBS, 100 IU/mL penicillin, 100 mg/mL streptomycin and 1 mmol/L sodium pyruvate, and then incubated at 37°C in a humidified atmosphere of 5% CO 2 . Cells were grown to 70%‐80% confluence before drug treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Human U-87 MG glioblastoma cells were kindly provided by Professor Ruei-Ming Chen, Graduate Institute of Medical Sciences, College of Medicine, Taipei Medical University and used for this study. Cells were cultured in Minimum Essential Medium Eagle's medium supplemented with 10% fetal bovine serum, 1% penicillin-streptomycin (10,000 U/ml) and 1% sodium pyruvate (100 mM) at 37˚C in a humidified incubator with 5% CO 2 (10).…”
Section: Methodsmentioning
confidence: 99%
“…Breast tumors showed an improved response with a delayed recurrence [119]. In addition, an induced cancer stem cells population was retarded by bevacizumab treatment [119,120]. Clinically, a phase I trial in patients with advanced, refractory malignancies including breast and lung cancers demonstrated that the inhibition of angiogenic activity was achieved by a combination of bortezomib, an agent that inhibits HIF-1α, with a bevacizumab regimen [121].…”
Section: Targeting Hypoxiamentioning
confidence: 99%